The Health Promotion Strategy To Increase Covid-19 Vaccination Coverage In Lampeapi Health Center: Health Promotion Strategy - Tasnim Tasnim; Siti Rahmatia (STIKes Mandala Waluya Kendari, 2023)
Background: Covid-19 vaccination coverage is low, especially for the 2nd and 3rd vaccination at the Lampeapi Health Center, Konawe Islands Regency. Therefore it is important to identify a health promotion strategy that can solve the above problems. The purpose of this study is to identify health promotion strategies which include regional policies, atmosphere building and the empowerment process at the Lampeapi Health Center in order to increase vaccination coverage in the Covid-19 pandemic era. Methods: This qualitative research recruited key and main informants which included the head of the health office, the leadership of the puskesmas, health promotion officers and community tokens in the Lampeapi Health Center area. This research was conducted in June 2022 at the Lampeapi Health Center, Konawe Islands District. Results: Regional policies to support the increase in vaccinations, namely accelerating vaccination in target areas; Budget availability for vaccinations; Formation of a Task Force; Imposition of Sanctions; and Availability of health promotion budget, facilities and infrastructure. While fostering the atmosphere includes socialization across sectors; Outreach to the community; Partnership with religious leaders; and build cross-sector communication. For the community empowerment strategy, namely education to the community; Assistance to Covid-19 volunteers; Mapping of Covid-19 vaccination data; forming a Covid-19 Task Force or volunteers; and Partnerships with NGOs or community organizations. Conclusions: The health promotion strategy in order to increase vaccination coverage at the Lampeapi Health Center is carried out through the support of local policies, building a conducive atmosphere, and community empowerment involving volunteers and NGOs.